TECHNOLOGICALLY ENHANCED ONLINE OPPORTUNITIES FOR LANGUAGE LEARNING IN INCLUSIVE EDUCATION - A. Raluy (Естетика і етика педагогічної дії)
The article deals with T the technologically enhanced online opportunities for language learning in inclusive education.  The author supposes theoretical background of the issue to be processes of globalization and digitalization, and  as the result - learners need to be additionally aware of human rights and to act as cultural agents, contributing to a more peaceful and tolerant cultural existence.